Pengembangan Media Pembelajaran Statistika Deskriptif Berbasis Website Edukasi dengan Pendekatan Problem-Based Learning untuk Meningkatkan Pemahaman Matematis Siswa SMA - Gisty, Rival Ananda; Tarigan, Gita Helena; Adhawina, Raissya; Tampubolon, Stephani Theresa Vania; Lubis, Sutan Ismail Akbar Rafsanjani; Siregar, Sutan Surya Darpan (Papanda, 2026)
Statistics is often considered difficult by high school students because the learning approach tends to be theoretical and less interactive, resulting in students' low mathematical understanding of concepts such as mean, median, and mode. This study aims to develop educational website-based learning media with a Problem-Based Learning (PBL) approach to improve students' mathematical understanding. The research method uses the Research and Development (R&D) model with the adoption of the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. The research subjects were grade XI students of Imelda Private High School Medan who were divided into an experimental class (using PBL website media) and a control class (conventional method). Data were collected through validation sheets, student response questionnaires, and mathematical understanding tests (pre-test and post-test). The results of the website media were declared